Language Proficiency and Student Performa nce in English-Speaking Country Medical Schools: A Mini Review - Winny Setyonugroho, Iman Permana (IISTE, 2015)
Background. An increasing numbe r of students, who is not a native speaker, enroll in healt care courses in 'western' country, raised concern regarding potential difficulties associated with English proficiency and academic performance. The auth ors set out to determine the extent to which the E nglish language proficiency of student who are not native English speakers affect the performance.Summary. Research paper descr ibing language proficiency and medical student per formance were identified from Pubmed and ProQ uest Education Databases. Thirteen papers were analyze d. There are two phases of education found in paper s, undergraduate and postgraduate. Regarding language proficiency, nine papers had English as a second language as variable while the rest using standardized language test. Two studies concluded that the standar dized test in language proficiency alone was not sufficient to adequately assess 'a non-native speaker'. Conclusion. There is a clear correlation between language proficiency and medical studen ts performance. Even more, understanding culture is important too. Sensitive issue could arise because o f this. Educator should not fear to analyze and judge student performance in the context of English-s peaking statues. Training in social skills might have a good influence in student acquisition of second langua ge.